Initial experience with precipitating hydrophobic injectable liquid in cerebral arteriovenous malformations. Issue 1 (February 2019) - Sirakov, Stanimir S; Sirakov, Alexander; Minkin, Krasimir; Hristov, Hristo; Ninov, Kristian; Penkov, Marin; Karakostov, Vasil; Orlov, Kirill; Gorbatykh, Anton; Kislitsin, Dmitry; Raychev, Radoslav
Background: Precipitating hydrophobic injectable liquid is a newly introduced liquid embolic agent for endovascular embolization with some technical advantages over other liquid embolic agents. We present our initial experience with precipitating hydrophobic injectable liquid in the endovascular treatment of cerebral arteriovenous malformations. Methods: From October 2015 to January 2018, 27 patients harboring cerebral arteriovenous malformations underwent endovascular embolization with precipitating hydrophobic injectable liquid 25. Clinical features, angiographic results, procedural details, complications, and follow-up details were retrospectively analyzed. Results: Twenty-seven patients with cerebral arteriovenous malformations were included. Total obliteration in one endovascular session was confirmed for 14/27 (52%) patients. Partial embolization was attained in 13 patients (48%) in whom staged treatment with following radiosurgery or surgery was planned. No mortality was recorded in this series. Complications during or after the embolization occurred in six of 27 (22.2%) patients. Conclusion: In our initial experience, precipitating hydrophobic injectable liquid has acceptable clinical outcome comparable to other liquid embolic agents. Although this is the largest reported study in arteriovenous malformation treatment with precipitating hydrophobic injectable liquid, further studies are needed to validate its safety and efficacy.